2023
DOI: 10.1007/s40948-023-00569-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on mechanical parameters and creep seepage characteristics of different coal and rock combination samples

Abstract: Based on the fact that the production of deep coalbed methane (CBM) in Yushe-Wuxiang Block is lower than expected, the paper is carried out uniaxial strength test and triaxial rheological test on coal measure strata reservoirs (mudstone, coal, sandstone and their composite sample) deeper than 1300 m in the block. In the uniaxial strength test, it is found that the stress–strain process of deep coal rock sample was similar to that of shallow one. The brittleness of deep coal rock sample is more obvious. It can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The creep constitutive models, as one of the key topics in the time-dependent studies of rocks, have attracted significant research (Sharifzadeh et al 2013). In previous decades, many constitutive models were proposed through empirical, component, and mechanism-based models, and scholars demonstrated that the creep behavior of rock shows significant nonlinear properties (Li et al 2020b;Zhao et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The creep constitutive models, as one of the key topics in the time-dependent studies of rocks, have attracted significant research (Sharifzadeh et al 2013). In previous decades, many constitutive models were proposed through empirical, component, and mechanism-based models, and scholars demonstrated that the creep behavior of rock shows significant nonlinear properties (Li et al 2020b;Zhao et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al established a damage constitutive model of rock-coal and rock-coal-rock composite samples by connecting the damage body with Newtonian body [23]. In addition, the effects of interface angle, prefabricated fractures, confining pressure, and loading rate on the strength and failure characteristics of rock-coal composite samples were studied [24][25][26][27][28]. The lithology, strength, and combined forms of coal and rock bodies have an important influence on the deformation and failure of CRCs.…”
Section: Introductionmentioning
confidence: 99%